Design And Development of a Narrative Based Tabletop Game for Promoting Soft Skills Acquisition in Technical Students in The South African Context - Lance R Bunt; Jacob J. Greeff (Bina Nusantara University, 2020)
A serious tabletop game called â€œGr8 Success!â€ has been developed for an undergraduate Communication skills module at the North-West University (NWU) in South Africa. This paper presents the details of the development process and discusses the first play tested prototype of the serious game in question. The game is described in the context of a conceptual framework being developed by researchers at the Serious Game Institute of South Africa (SGI-SA).